DEVELOPING ATTITUDES ON GLOBAL AWARENESS INSTRUMENT OF SENIOR HIGH SCHOOL’S STUDENTS - AMAN ABADI NUGRAHA (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2018)
This study developed the attitudes on global awareness instrument of senior high school’s students. It used Research and Development (R&D) design which consisted of preliminary phase, product development, and product implementation (field test). The data were collected from 20 panels, the first phase of field test which consist of 250 students, and the second phase of field test which consist of 265 students . The data were analyzed by using factor analysis with Confirmatory Factor Analysis (CFA) method. The result of this study indicated that the standardized attitudes on global awareness instrument consist of 55 items with cognition, conation, and affection dimension with Composite Reliability (CR) was 0,933 and Variance Extracted (VE) was 0,824.